Assessing the self-disclosure of clients and length of conversation with a counselor in a gender dyad - Magno, Carlo (Philippine Journal of Counseling Psychology, 2009)
The gender and gender role identity of the client was varied and each variation was matched with a male or female counselor. The clients' length of conversation and degree of client self-disclosure was assessed. The design of the study is factorial (2 X 2 X 2) in which gender (male and female) and gender role (androgynous and sex type) of the client with the counselor's gender were varied in a dyad. There were 80 respondents, 40 males and 40 females who were randomly assigned to a male or female counselor. The clients' gender role identity was identified using the Ben Sex Role Inventory. The participants were requested to participate in a psychological interview over the telephone and their conversations were recorded with permission. Clients' self disclosure was assessed by eaters and the length of conversation was timed in minutes. The results showed that females (M=49.99) self disclose more as compared to males (M=47.6) regardless of the counselor's gender. Also androgynous (M=51.61) clients significantly self-disclose more as compared to sex types (M=46.03). Androgynous female clients with a male counselor had the highest self-disclosure (M=50.23). Self-disclosure of the client significantly increases as the interview session becomes longer (r=.36).